A doubter's guide to world religions : a fair and friendly introduction to the history, beliefs, and practices of the big five - Dickson, John P., 1967- (Grand Rapids Zondervan, 2022)
"A Doubter's Guide to World Religions presents each of the world's five major religions and carefully outlines the history, belief systems, and spiritual practices of Hinduism, Buddhism, Judaism, Christianity, and Islam so that the interested and curious doubters can explore their similarities and differences"--
Includes bibliographical references and index.
Keywords: Religions